New protosirenid (Mammalia, Sirenia) in the late Eocene sea cow assemblage of southwestern Morocco. (May 2022) - Zouhri, Samir; Zalmout, Iyad S.; Gingerich, Philip D.
Abstract: Two sirenian species are present in the late Eocene Samlat Formation near Ad-Dakhla in southwestern Morocco. A well preserved mandible with left and right dentaries belongs to a new protosirenid genus and species Dakhlasiren marocensis closely related to the genus Protosiren . An early dugongid of uncertain identification (cf. Eotheroides sp.) is also present, represented by vertebrae and ribs. Protosirenids differ from dugongids in the form of the brain, size and separation of nasal bones, and conformation of the anterior mandible. Protosirenids also differ in having vertebrae with larger neural canals, in having ligamentous rib articulations, and in lacking the pachyostotic ribs characteristic of dugongids. We tentatively interpret the latter differences to be related to feeding on softer vegetation farther offshore, with a thoracic rete mirabile for counter-current heat exchange and a collapsible rib cage to enable deeper dives. Dakhlasiren seemingly carried the divergent specializations of Protosiren a step farther by reduction of tongue musculature and loss of a masticatory surface at the front of the mandible. Highlights: The Samlat Formation in southwestern Morocco yields a new Eocene sirenian assemblage. Fossils described here include a new genus and a new species of Protosirenidae. The protosirenid mandible has particular physiological and ecological adaptations. These adaptations differ from all known protosirenids and contemporary dugongids. Morphological differences between Protosirenidae and Dugongidae are clarified.